Pendampingan Pengembangan Kurikulum Terpadu pada Binar Ilmu Boarding School Cimenyan Bandung - Uyun, Aip Syepul (Ma'soem University, 2022)
This article provides a brief description on how to conduct curriculum development in educational institution. This measure has a significant position in our educational system. Curriculum development is a comprehensive process for determining the needs of a group of learners and for developing the aims or objectives of a school. This is manifested in the form of subject structures, teaching methods, and materials, as well as the evaluation process. This community service was carried out directly by evaluating the existing curriculum. Curriculum development activities were conducted in two months. The curriculum was discussed with the teachers and revised and adapted to the needs of institution at at Binar Ilmu Boarding School, Cimenyan, Bandung. The Participants were all teaching staff and all stakeholdrer school. This activities were caried out in three major stage. It was evaluating existing curriculum, revitalizing the existing curriculum and finishing. From those activities, it was produced the new curriculum of institution namely BIBS Curriculum.